Scientific Sources and Teaching Contexts Throughout History: Problems and Perspectives - Bernard, Alain (Boston Studies in the Philosophy and History of Science, 2014)
Making clear the meaning of "context" and highlighting the complexity hidden in the words "teaching" and "learning", this book presents comparatist approaches and emphasizes the notion of teaching as projects embedded in coherent treatises or productions